EPIC3, a novel Ca2+ indicator located at the cell cortex and in microridges, detects high Ca2+ subdomains during Ca2+ influx and phagocytosis. (December 2020) - Roberts, Rhiannon E.; Vervliet, Tim; Bultynck, Geert; Parys, Jan B.; Hallett, Maurice B.
Graphical abstract: Highlights: An low Ca 2+ affinity GECI-ezrin construct, EPIC3, was developed as a novel indicator of Ca 2+ at the cell cortex. Using EPIC3, Ca 2+ influx was found to elevate Ca 2+ concentrations at the cell cortex, as high as 30−80μM. Similar high concentrations of Ca 2+ were found at the leading edge of motile cells and in phagocytic pseudopodia. Highly localised high Ca 2+ domains near the closed phagosome were also evident. The release of ezrin from cell surface wrinkles occurred at [Ca 2+ ]> 20μM. Abstract: The construction of a low affinity Ca 2+ -probe that locates to the cell cortex and cell surface wrinkles, is described called. EPIC3 (e zrin-p rotein i ndicator of C a 2+ ). The novel probe is a fusion of CEPIA3 with ezrin, and is used in combination with a Ca 2+ -insensitive probe, ezrin-mCherry, both of which locate at the cell cortex. EPIC3 was used to monitor the effect of Ca 2+ influx on intra-wrinkle Ca 2+ in the macrophage cell line, RAW 264.7. During experimentally–induced Ca 2+ influx, EPIC3 reported Ca 2+ concentrations at the cell cortex in the region of 30−50 μM, with peak locations towards the tips of wrinkles reaching 80 μM. These concentrations were associated with cleavage of ezrin (a substrate for the Ca 2+ activated protease calpain-1) and released the C-terminal fluors. The cortical Ca 2+ levels, restricted to near the site of phagocytic cup formation and pseudopodia extension during phagocytosis also reached high levels (50−80 μM) during phagocytosis. As phagocytosis was completed, hotspots of Ca 2+ near the phagosome were also observed.